Performance of electrocoagulation and electro-Fenton processes for treatment of nanofiltration concentrate of biologically stabilized landfill leachate - Guvenc, Senem Yazici; Dincer, Kaan; Varank, Gamze (ELSEVIER, 2019)
In the present work, experimental study for leachate nanofiltration concentrate treatment by electrocoagulation and electro-Fenton processes using iron electrodes was carried out in a batch electrolytic reactor. Removal efficiencies of 60.2% for total organic carbon (TOC), 69.4% for chemical oxygen demand (COD), and 87.6% for color from the electro-Fenton process at the optimum operating conditions and 45% for TOC, 57.4% for COD, and 77.1% for color from the electrocoagulation process at the optimum operating conditions respectively, were obtained. Additionally the fraction of biodegradable COD increased from 6.37% to 17.04% and 30.08% after electrocoagulation and electro-Fenton processes respectively. About 39% soluble COD and 82% particulate COD removal efficiencies were obtained by electrocoagulation whereas 57% soluble COD and 81% particulate COD removal efficiencies were obtained by electro-Fenton process. Electro-Fenton process was found to be more effective than the electrocoagulation process with respect to the removal efficiencies of COD and TOC. However both processes could be efficient methods for converting nonsoluble COD to soluble COD and removal of non-biodegradable COD. As a result both of the processes could be used as a post-treatment method for leachate and an effective method inert COD removal from leachate nanofiltration concentrate.
Keywords: Leachate nanofiltration concentrate; Electrocoagulation; Electro-Fenton; COD fractions; WASTE-WATER TREATMENT; DISSOLVED ORGANIC-MATTER; MONOPOLAR ELECTRODES; COD REMOVAL; EC PROCESS; OPTIMIZATION; DEGRADATION; OXIDATION; BIODEGRADABILITY; COAGULATION; Engineering; Water Resources